2007
DOI: 10.1111/j.1742-4658.2007.05731.x
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody, PGM34, against 6‐sulfated blood‐group H type 2 antigen, on the carbohydrate moiety of mucin

Abstract: Mucin, a major component of mucus, is a highly O‐glycosylated, high‐molecular‐mass glycoprotein extensively involved in the physiology of gastrointestinal mucosa. To detect and characterize mucins derived from site‐specific mucous cells, we developed a monoclonal antibody, designated PGM34, by immunizing a mouse with purified pig gastric mucin. The reactivity of PGM34 with mucin was inhibited by periodate treatment of the mucin, but not by trypsin digestion. This suggests that PGM34 recognizes the carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…In case of B. longum BB536 and B. bifidum ATCC29521, the findings of assays studying the effect of enzymatic treatments agreed with those of the adhesion inhibition test performed using PGM34 and HCM31 mAbs, which react the 6-sulfated blood-group H type 2 antigen and the Sd a blood group antigen, respectively. 22,23) The epitope of PGM34 or HCM31 may be essential for the adhesion of B. longum BB536 and B. bifidum ATCC29521. Although pretreatment with sulfatase reduced the adhesion of B. animalis subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of B. longum BB536 and B. bifidum ATCC29521, the findings of assays studying the effect of enzymatic treatments agreed with those of the adhesion inhibition test performed using PGM34 and HCM31 mAbs, which react the 6-sulfated blood-group H type 2 antigen and the Sd a blood group antigen, respectively. 22,23) The epitope of PGM34 or HCM31 may be essential for the adhesion of B. longum BB536 and B. bifidum ATCC29521. Although pretreatment with sulfatase reduced the adhesion of B. animalis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…22,23) ELISAs were performed according to the method described by Tsubokawa et al, 22) with the following modifications. A 96-well microplate was coated with 0.1-500 μg/mL of our prepared mucin samples (100 μL/well), followed by blocking with phosphate-buffered saline (PBS) containing 5% (w/v) skim milk for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The epitope of this mAb includes a specific acid residue of mucin [21] and the epitope of PGM34 includes a specific sulfated oligosaccharide of the mucin molecule. This mAb stains almost all of the goblet cells of rat small intestine [22]. For the simultaneous detection of sulfated and non-sulfated sialomucins in intestinal epithelium, high-iron diamine-Alcian blue (pH 2.5) staining (HID-AB) and anti MUC2 polyclonal antibody (Santa Cruz Biotech, CA) immunostaining were also performed.…”
Section: Histological and Immunohistochemical Examinationmentioning
confidence: 99%
“…In our previous studies, we have reported quantitative and qualitative changes in gastric mucin, a major component of mucus, in normal and diseased animals as well as in humans, and have demonstrated the importance of the role of mucin in the gastric mucosal barrier [16][17][18]. We have also established several mAbs that react with mucin synthesized and secreted from specific mucus-producing cells of the rat gastrointestinal (GI) mucosa [19][20][21][22]. But only a few cases are reported regarding the alteration of mucin content of the small intestine.…”
mentioning
confidence: 93%
“…The mAbs RGM21 and HIK1083, which recognize a specific carbohydrate portion of rat gastric surface-and gland-type mucins, respectively (Ishihara et al, 1996a(Ishihara et al, , 1996b, are frequently used to characterize the different mucin molecular structures. From histological studies and epitope analyses, the characteristics of each antibody have been elucidated (Goso et al, 1999(Goso et al, , 2003Tsubokawa et al, 2007Tsubokawa et al, , 2009). …”
Section: Development Of Monoclonal Antibody Against Gastric Mucinmentioning
confidence: 99%